Targeting Subsets of Mammalian Neurons - Boris V. Zemelman (Neuroscience Insights, 2020)
Functional dissection of mammalian neuronal circuits depends on accurate targeting of constituent cell classes. Transgenic mice offer precise and predictable access to genetically defined cell populations, but there is the pressing need to target neuronal assemblies in species less amenable to genomic manipulations, such as the primate, which is an important animal model for human perception, cognition, and action. We have developed several virus-based methods for accessing all forebrain inhibitory interneurons as well as the major excitatory and inhibitory neuron subclasses. These methods rely on the wealth of emerging single-cell transcriptome data and harness gene expression variations to refine neuron targeting. Our approach enables nuanced functional studies, including in vivo imaging and manipulation, of the diverse cell populations of the mammalian neocortex, and it represents a timely blueprint for transgenics-independent interrogation of functionally significant cell classes.